1999
DOI: 10.2527/1999.7792517x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter gene expression in bovine mammary gland.

Abstract: Transport of glucose across the plasma membrane of mammary epithelial cells is believed to be a passive process of facilitated diffusion mediated by facilitative glucose transporter(s). This article presents three lines of evidence that indicate the expression of sodium/glucose cotransporter (SGLT1) in the mammary gland of lactating and nonlactating cows. First, transcripts of SGLT1 mRNA ranging in size from 1.5 to 5.2 kb were detected in polyadenylated RNA preparations of mammary glands of lactating and nonla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…GLUT1 is a receptor of HTLV infection in CD4+T cells [37], and HIV-1 infection in CD4+T cells is abrogated in the absence of surface GLUT1 [40]. Recent studies [7], [22], [41], [42] have found that GLUT1 is most abundantly expressed in mammary glands and that the levels increase during pregnancy and peak during lactation, results that may be related to the abundant synthesis of proteins and lactose in breast tissue. In this study, using breast epithelial cells, the data for glucose uptake in the GT1-GMGE cells confirmed that the cloned GLUT1 possesses glucose transport activity, a result that corresponded to the high expression of GLUT1 mRNA in the GT1-GMGE cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLUT1 is a receptor of HTLV infection in CD4+T cells [37], and HIV-1 infection in CD4+T cells is abrogated in the absence of surface GLUT1 [40]. Recent studies [7], [22], [41], [42] have found that GLUT1 is most abundantly expressed in mammary glands and that the levels increase during pregnancy and peak during lactation, results that may be related to the abundant synthesis of proteins and lactose in breast tissue. In this study, using breast epithelial cells, the data for glucose uptake in the GT1-GMGE cells confirmed that the cloned GLUT1 possesses glucose transport activity, a result that corresponded to the high expression of GLUT1 mRNA in the GT1-GMGE cells.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 has a ubiquitous distribution in tissues and culture cells [5][7] and is considered to be the primary transporter responsible for basal glucose uptake. GLUT1 expression is detected abundantly in the mammary gland [8] and increases during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of glucose in lactating ruminants, the mechanisms underlying the regulation of glucose uptake into the mammary gland and subsequent utilization are subject of this research. The effects of manipulated glucose concentrations on mammary glucose transporters were mostly investigated in vitro (Zhao et al., ; Xiao and Cant, ), while in vivo studies focused on changes in gene expressions of glucose transporters during the lactation–gestation cycle in lactating dairy cows (Zhao and Keating, ,b; Mattmiller et al., ). Altered plasma glucose concentrations do not only affect glucose transporters in the mammary gland, but have also an impact on genes involved in the synthesis of milk constituents (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However; a lactating mammary gland cannot synthesize glucose from other precursors due to the absence of glucose-6-phosphatase (Threadgold and Kuhn 1979) and so is dependent on the blood supply for its glucose requirement. Mammary glucose uptake, which is performed by both active and passive transport processes (Zhao et al 1999(Zhao et al , 2005, is independent of the concentration of glucose and insulin in the arterial blood during lactation. It has also been suggested that the blood glucose concentration affects the rate of synthesis of milk lactose, hence milk volume by osmotic association (Kronfeld 1982).…”
Section: Introductionmentioning
confidence: 99%